ANALISIS TINGKAT LITERASI EKONOMI MAHASISWA IPS UNIVERSITAS ISLAM RADEN RAHMAT MALANG - Hendra Rustantono (Institut Pendidikan Tapanuli Selatan, 2022)
AbstractMaking good economic and financial decisions is the right choice and it is necessary to understand how to do the right and smart and think right in making economic decisions in everyday life. This study intends to describe the level of economic literacy of social studies students for the 2018-2021 academic year, Raden Rahmat Islamic University, Malang. The population and sample in this study were 58 social studies students class 2018-2021. This research is a survey research with question-based data collection techniques distributed to students who have taken the Introduction to Economics course. The data analysis method used in this research is descriptive analysis. In this study, it was found that the level of economic literacy of social studies students for the 2018-2021 academic year was in the medium category, which was 60-80% (>60%). When viewed from the number of students who answered correctly, 39% of the total social studies students from the 2018-2021 class were 58 students. This shows that social studies education students from the 2018-2021 class of Islamic University Raden Rahmat Malang can make good economic and financial decisions in their daily lives and become smart consumers and act with the right way of thinking.